Clinical efficacy analysis of intelligent pressure-controlled ureteroscopy combined with thulium laser in the treatment of isolated upper urinary tract urothelial carcinoma - Chen, Hua; Xiao, Jiansheng; Ge, Jiaqi (Frontiers in Oncology, 2024)
ObjectiveThis study aims to investigate the clinical treatment effect of intelligent pressure-controlled ureteroscopy combined with thulium laser for patients with isolated kidney upper tract urothelial carcinoma (UTUC).MethodsThis study employed a retrospective analysis approach and focused on six patients with isolated kidney UTUC admitted to our hospital from June 2018 to May 2023, who underwent tumor resection surgery using intelligent pressure-controlled ureteroscopy combined with thulium laser. We collected the perioperative clinical data of these six patients and conducted statistical analysis of the treatment effects.ResultsThe surgeries of all six patients were completed smoothly, without incidents of surgery termination due to significant bleeding. Postoperative pathology revealed that four patients had low-grade non-invasive papillary urothelial carcinoma, while the other two patients had high-grade invasive urothelial carcinoma. During follow-up period, one patient had a renal pelvis recurrence three months after the surgery, and subsequently underwent thulium laser resection. Additionally, another patient experienced bladder recurrence eight months after the surgery and received transurethral resection of bladder tumor (TURBT) for treatment. The remaining four patients did not experience tumor recurrence during the follow-up.ConclusionFor patients with isolated kidney associated with UTUC, intelligent pressure-controlled ureteroscopy combined with thulium laser represents a feasible treatment option, with good therapeutic effects for low-risk upper tract urothelial carcinoma.